Searching for Information Research: A bibliometric analysis celebrating 30 years of a pioneering open access journal (1995-2024) - Nelhans, Gustaf; Lindelöw, Camilla; Lillo Cea, Pablo; Scirone, Marco; António , Rui José; Hammarfelt, Björn (Information Research an international electronic journal, 2025)
Introduction. This paper analyses the presence of the journal Information Research in traditional citation databases, such as Web of Science, as well as in new open sources like OpenAlex; and services tracking policy and technological impact, such as SciVal and Overton. Method. We analyse the visibility of the journal across sources. With the limitations of representation in the different sources we proceed to study the impact of the journal in the scholarly community, as well as in society, by looking at how Information Research papers are situated in the scholarly world and how they are cited in patents and policy papers. Finally, we look at the openness of the journal as seen through the data sources. Results. Our results show that Information Research has made quite a journey. It has found a place in the scholarly universe: authors from institutions from around the world publish there and other prestigious journals cite the content. The content coverage in the perused data sources could be improved, as can metadata, for example markup of article types. Conclusions. Whilst the journal has been openly available on the Internet throughout its history, this is not well reflected in the data sources. This is something that the new home, Publicera.kb.se, might help with. Larger platforms can help individual journals fulfil the data standards needed to be properly indexed in the large data sources.